2006
DOI: 10.1111/j.1083-6101.2003.tb00223.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperlink Analyses of the World Wide Web: A Review

Abstract: We have recently witnessed the growth of hyperlink studies in the field of Internet research. Although investigations have been conducted across many disciplines and topics, their approaches can be largely divided into hyperlink network analysis (HNA) and Webometrics. This article is an extensive review of the two analytical methods, and a reflection on their application. HNA casts hyperlinks between Web sites (or Web pages) as social and communicational ties, applying standard techniques from Social Networks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
173
0
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(181 citation statements)
references
References 120 publications
1
173
0
7
Order By: Relevance
“…Nevertheless, network analysis using MENA nations as nodes has also been useful for studying their network of telephone call traffic (Danowski, 2000) and Internet development in relation to civil society development (Danowski, 2011). The current research includes network analysis of MENA and MM nations based on the number of hyperlinks (Park & Thelwall, 2003;Park, 2010;Barnett, Chung, & Park 2011) on Web pages in one nation's domain that are pointing to pages in another nation's domain. In addition, we analyze words as nodes for semantic network analysis using the same analytical framework to investigate changes in the semantic associations of the ideological catchword of "Jihad.…”
Section: Network Analysismentioning
confidence: 99%
“…Nevertheless, network analysis using MENA nations as nodes has also been useful for studying their network of telephone call traffic (Danowski, 2000) and Internet development in relation to civil society development (Danowski, 2011). The current research includes network analysis of MENA and MM nations based on the number of hyperlinks (Park & Thelwall, 2003;Park, 2010;Barnett, Chung, & Park 2011) on Web pages in one nation's domain that are pointing to pages in another nation's domain. In addition, we analyze words as nodes for semantic network analysis using the same analytical framework to investigate changes in the semantic associations of the ideological catchword of "Jihad.…”
Section: Network Analysismentioning
confidence: 99%
“…In particular, Jackson had concerns whether nodes in a hyperlink network (pages or sites) could reasonably be described as social actors and also whether a hyperlink network could satisfy one of the core assumptions of SNA -the interdependence of actors. Other authors have similarly expressed caution about the potential use of hyperlink networks for social science research, with Park and Thelwall (2003) noting that hyperlink data can be used to 'potentially discern fingerprints of social relations has suggested that hyperlink data may need to be supplemented by other data and methods (for example, interviews) in order for a website to be equated with a node and a hyperlink to be equated with a tie, and social network analysis techniques applied.…”
Section: Hyperlink Network Analysismentioning
confidence: 99%
“…For instance, the relationships among web domains have been analyzed in the Nordic academic web space (Ortega and Aguillo, 2008), or even in the world web space (Ortega and Aguillo, 2009). Typically, SNA has been frequently used for the study of link analysis (Park and Thelwall, 2003;Toral et al, 2010). SNA is a set of research procedures for identifying structures in social systems based on the relations among the system components, also referred to as nodes.…”
Section: Wsmmentioning
confidence: 99%
“…Although some alternatives based on content analysis have been proposed in the literature (Toral et al, 2009a), Park and Thelwall (2003) states that, "compared to other web methods such as a content-based analysis, the relative advantage of hyperlink analysis is that it is able to examine the way in which web sites form a certain kind of relations with others via hyperlinks," and "using this information in combination with other web analyses can contribute to the understanding of why and how certain types of contents come to appear on web sites." Potgieter et al (2007) indicates that SNA is a research area aimed at understanding social complexity by representing and analyzing social networks using mathematical graphs.…”
Section: Wsmmentioning
confidence: 99%